2005
DOI: 10.1093/ajcn/81.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of seasonality on preterm birth and intrauterine growth restriction in rural Africans1–4,

Abstract: We conclude that a reduction in LBW in such communities may require multiple interventions because of the variety of precipitating factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
140
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 34 publications
7
140
0
2
Order By: Relevance
“…The different compositions of the cohorts may explain why we found higher responses in infants born in the wet season and infants whose mothers had a relatively low BMI and why these effects were independent of the birth weight of the infants, while the previous studies found inhibition of immune responses associated with birth in the wet season and prenatal undernutrition (27)(28)(29)39).…”
Section: Discussionmentioning
confidence: 55%
“…The different compositions of the cohorts may explain why we found higher responses in infants born in the wet season and infants whose mothers had a relatively low BMI and why these effects were independent of the birth weight of the infants, while the previous studies found inhibition of immune responses associated with birth in the wet season and prenatal undernutrition (27)(28)(29)39).…”
Section: Discussionmentioning
confidence: 55%
“…Dietary supplementation during pregnancy with resultant maternal weight gain and markedly increased birth weight was demonstrated in conditions of acute food shortage (Stein et al, 1975;Rayco-Solon et al, 2005). However, under conditions of chronic undernutrition, supplementation of energy, proteins as well as micronutrients to the level of recommended dietary allowance during pregnancy resulted in only marginal improvements in birth weight (Christian et al, 2003;Kramer and Kakuma, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometry and mortality in infants in rural Gambia Martha K Mwangome et al [32][33][34] The anthropometric data described in this study were collected by trained health workers (nurses and midwives) during monthly well baby clinics (established in Keneba in 1975), during postnatal care clinic visits (at 6 weeks and 3 months of age), or through the periodic DSS survey. Hospital deaths were ascertained using hospital records and home deaths using village informants.…”
Section: Researchmentioning
confidence: 99%